Aesthetics Assessment and Patient Reported Outcome of Nasolabial Aesthetics in 18-Year-Old Patients With Unilateral Cleft Lip - Mulder, Frans J. (Cleft Palate Craniofac J, 2019)
OBJECTIVE: To determine if there is a correlation between objective nasolabial aesthetics assessment using the Cleft Aesthetic Rating Scale (CARS) and patient satisfaction. DESIGN: Retrospective analysis of a generic satisfaction questionnaire and independent assessment by three cleft surgeons of the nasolabial area of these patients on 2D frontal photographs, using the CARS. SETTING: The Vrije Universiteit Medical Center and The Academic Center for Dentistry Amsterdam. PATIENTS: Thirty-nine 18-year old patients with a repaired complete or incomplete unilateral cleft lip, with or without a cleft palate, and a completed satisfaction questionnaire. Exclusion criteria were an incomplete questionnaire; a history of facial trauma; and congenital syndromes affecting facial appearance. MAIN OUTCOME MEASURES: The correlation between surgeon evaluation (on a 5-point Likert scale) and patient satisfaction (not, moderately or very satisfied) on nasolabial appearance was assessed using Spearman rho (ρ). RESULTS: There was a negligible correlation between surgeon evaluation and patient satisfaction on nose assessment (ρ = 0.20) and a moderate correlation on lip assessment (ρ = 0.32). CONCLUSIONS: Most literature supports this discrepancy between different objective aesthetics evaluation methods and subjective patient-reported outcome measures, suggesting there are factors playing a role in patient satisfaction that are impossible to objectify with assessment methods. Therefore, a strong emphasis should remain on clear communication between the physician and patient regarding their expectations, perception, and satisfaction of surgery results.